STRATEGI KOMUNIKASI UNTUK MENCIPTAKAN KAWASAN PANTAI YANG BERSIH DARI SAMPAH (STUDI KASUS TAPLAU PADANG) - Yuni Candra; Susi Evanita (Ensiklopedia Social Review, 2021)
Waste management so far has not been optimally carried out because it is not in accordance with environmentally sound waste management methods and techniques so that it has a negative impact on the cleanliness of the coastal area and the environment becomes dirty. The waste problem has become a national problem, so that its management needs to be carried out in a comprehensive and integrated manner from upstream to downstream in order to provide economic benefits, be healthy for the community, and safe for the environment, and can change people's behavior. This can be seen from the conditions in Taplau Padang that waste management is still not running optimally. The condition of waste in coastal tourist areas in general has not been managed optimally even though it already has waste management components. In fact, many cleaning managers face problems and obstacles that result in services that are not in accordance with the technical provisions and expectations of tourists. Taking into account the condition of the waste, the activities of throwing garbage to the seaside or littering have been going on for a long time by the people around Taplau Padang. Because some of the garbage has mixed with the ground and a lot of it settles on the beach and around the beach. As a result, there is a view that is not good to see and be seen by tourists who are in Taplau Padang.